2019
DOI: 10.1515/ijfe-2018-0349
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sesame Oil Adulteration Using Low-Field Nuclear Magnetic Resonance and Chemometrics

Abstract: Identification of edible oil adulteration is an essential task for oil quality control. In this study, the adulteration of sesame oil samples with soybean oil was detected by low-field nuclear magnetic resonance (LF-NMR) combining with chemometrics including principal component analysis (PCA), partial least squares (PLS) and principal component regression (PCR) methods. PCA analysis was applied for the classification of various adulteration ratios of sesame oil samples. PLS and PCR were used for the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…For example, Ancora et al [ 21 ] demonstrated that LF-NMR relaxation measurements could be applied to determine the occurrence of adulteration in EVOO samples when mixed with four different edible vegetable oils. Moreover, Wang et al [ 22 ] applied this methodology to detect the adulteration of sesame oil samples with soybean oil, and the adulteration ratios were estimated using principal component analysis (PCA) and partial least squares (PLS). Similarly, Zhu et al [ 23 ] applied discriminant analysis (DA) for estimating the adulteration ratios of peanut oil adulterated with soybean oil, rapeseed oil, or palm oil based on LF-NMR relaxometry measurements.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ancora et al [ 21 ] demonstrated that LF-NMR relaxation measurements could be applied to determine the occurrence of adulteration in EVOO samples when mixed with four different edible vegetable oils. Moreover, Wang et al [ 22 ] applied this methodology to detect the adulteration of sesame oil samples with soybean oil, and the adulteration ratios were estimated using principal component analysis (PCA) and partial least squares (PLS). Similarly, Zhu et al [ 23 ] applied discriminant analysis (DA) for estimating the adulteration ratios of peanut oil adulterated with soybean oil, rapeseed oil, or palm oil based on LF-NMR relaxometry measurements.…”
Section: Introductionmentioning
confidence: 99%
“…a reduced test set and the rest as a reduced training set. The "reduced classification model" to evaluated the ideal number of PCs (Wang et al, 2019;. Among 65 samples, 25 samples were chosen as reduced test set and 40 samples were chosen as reduced training set.…”
Section: Pca and Fdamentioning
confidence: 99%
“…Meanwhile, combination of more than one chemometric tools has already been employed to detect the adulteration in blends. Wang et al (2019) used PCA partial least squares (PLS) and principal component regression (PCR) methods to detecting sesame oil adulteration based on low-field nuclear magnetic resonance data.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame oil is a seed oil extracted from Sesamum indicum L. Because it provides many health benefits and contains antioxidants, polyunsaturated fatty acids, tocopherols, sesamin and sesamol, which are cardioprotective functional components, it is becoming more popular and demanded worldwide (1,2). Sesame oil consists of up to 48% linoleic acid, 43% oleic acid, 12% palmitic acid, and 7% stearic acid (3).…”
Section: Introductionmentioning
confidence: 99%